The role of behavioral loyalty in youth development at summer camp. (1st January 2019) - Wilson, Cait; Sibthorp, Jim
Abstract: Behavioral loyalty, or consistent participation in summer camp, may impact how and in what ways young campers develop. Specifically, this study examines how two factors of behavioral loyalty, dosage (e.g., weeks at last camp) and developmental progression (e.g., transitioning from camper to camp employee), are associated with youth development attributed to the camp experience. Campers categorized as core participants (i.e., those reporting higher dosage and further developmental progression) were compared to fringe participants (i.e., those who reported lower dosage of camp and less developmental progression). As hypothesized, there were significant differences in development for core and fringe participants based on both dosage and developmental progression. Although both core and fringe participants benefited from camp, core participants reported greater development of measured outcomes such as relationship skills, appreciation for diversity, and self-identity. These findings offer insight into the benefits of increased behavioral loyalty in summer camp participants.